Between self-determination and the African union's position on uti possidetis : a legal analysis of Somaliland's secession claim - Fagbayibo, Babatunde Olaitan (University of Pretoria, 2025)
Mini Dissertation (LLM (International Law))--University of Pretoria, 2024.